2021
DOI: 10.3389/fgene.2021.755222
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Transcriptomic Atlas: A Comprehensive Analysis of COVID-19 Related Transcriptomics Datasets

Abstract: Background: To develop anti-viral drugs and vaccines, it is crucial to understand the molecular basis and pathology of COVID-19. An increase in research output is required to generate data and results at a faster rate, therefore bioinformatics plays a crucial role in COVID-19 research. There is an abundance of transcriptomic data from studies carried out on COVID-19, however, their use is limited by the confounding factors pertaining to each study. The reanalysis of all these datasets in a unified approach sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 43 publications
3
23
0
Order By: Relevance
“…The present study represents a follow-up of a recent report from our group [ 21 ] in which we performed an integrative analysis of transcriptional alterations in respiratory airways and peripheral blood leukocytes. This approach successfully developed by our and other groups [ 22 , 23 , 24 ] demonstrated multi-tissue systemic effects of SARS-CoV-2 infection, providing insightful mechanisms of SARS-CoV-2 pathology and cellular targets for therapy [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The present study represents a follow-up of a recent report from our group [ 21 ] in which we performed an integrative analysis of transcriptional alterations in respiratory airways and peripheral blood leukocytes. This approach successfully developed by our and other groups [ 22 , 23 , 24 ] demonstrated multi-tissue systemic effects of SARS-CoV-2 infection, providing insightful mechanisms of SARS-CoV-2 pathology and cellular targets for therapy [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…We previously noted that increased TLR3 signaling leads to reduced DISC1 expression and aberrant neurogenesis. A recent transcriptomics study of publicly available datasets demonstrated that DISC1 is downregulated by COVID-19 ( Alqutami et al, 2021 ). Though the exact role that DISC1 plays in complex mental disorders is unclear, DISC1 is an important component in the formation of the immune synapse.…”
Section: Discussionmentioning
confidence: 99%
“…DISC1 and the DISC1 pathway genes like PDE4B and NRXN1 are implicated in several mental health disorders ( Millar et al, 2007 ; Korth, 2009 ; Hu et al, 2019 ). PDE4B is found in the DISC1 interactome, and differential expression of PDE4B has also been noted in relation to COVID-19 infection ( Alqutami et al, 2021 ). PDE4B has been shown to regulate cytokine signaling pathways ( Lugnier et al, 2021 ; Moolamalla et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study found that knock down of MAP3K9 reduced SARS-CoV-2 virus replication [38]. DCLK2 is differentially expressed in SARS-CoV-2 patients [39]. AURKC would be an interesting candidate to investigate for its role in SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%